Why Do You Work as a Teacher? Associations Between Teachers’ Work Motivation, Teaching Quality, and Well-being - Šilinskas, Gintautas; Raižienė, Saulė (Psichologija, 2024)
This cross-sectional study investigated correlations between six types of work motivation (intrinsic motivation; integrated, identified, introjected, and external regulation; and amotivation), teaching quality, and well-being among primary school teachers. Forty Grade 3 teachers in Lithuania answered a questionnaire about their work motivation (six types), teaching quality (frequency of instruction and degree of affection), and well-being (self-efficacy and exhaustion). Concerning teaching quality, the results showed that both autonomous motivation (intrinsic motivation and integrated and identified regulation) and controlled motivation (introjected and external regulation) positively correlated with teachers’ frequency of literacy and math instruction, whereas only autonomous motivation positively correlated with teachers’ affection when interacting with their class. Regarding well-being, autonomous motivation positively correlated with self-efficacy, whereas amotivation positively correlated with exhaustion.
Keywords: Work Extrinsic and Intrinsic Motivation Scale (WEIMS); work motivation; teachers; teaching quality; well-being